Long Non-coding RNA LINC01787 Drives Breast Cancer Progression via Disrupting miR-125b Generation - Li, Yongzhen; Song, Ying; Wang, Zhihui; Zhang, Zheying; Lu, Manman; Wang, Yongxia (Frontiers in Oncology, 2019)
Breast cancer is still the most common and leading cause of cancer-related deaths in women worldwide. Long noncoding RNAs (lncRNAs) and microRNAs (miRNAs) have shown key regulator roles in various cancers. Previous reports have identified miR-125b as a critical tumor suppressor in breast cancer. However, the roles of lncRNAs in breast cancer are far from well-characterized. In this study, we identified a novel lncRNA LINC01787, which specifically binds pre-miR-125b, inhibits the binding between DICER and pre-miR-125b, represses the processing of pre-miR-125b by DICER, and therefore induces pre-miR-125b accumulation and represses mature miR-125b generation. Functional assays showed thatLINC01787 promotes breast cancer cell proliferation and migration and breast cancer xenograft growth in vivo, which were abolished by the mutation of pre-miR-125b binding sites on LINC01787 or overexpression of miR-125b. Furthermore, LINC01787 is up-regulated in breast cancer tissues and associated with advanced stages and poor survival. The expression of LINC01787 is inversely associated with that of miR-125b in breast cancer tissues. In conclusion, our findings identified a novel up-regulated and oncogenic lncRNA LINC01787 in breast cancer, which binds pre-miR-125b and represses mature miR-125b generation. Our data suggested LINC01787 as a potential prognostic biomarker and therapeutic target for breast cancer.